Infection by CagA Positive Helicobacter pylori among Dyspeptic, and Healthy Blood Donors in Tripoli city - Aziza Abdelgawad; Abdurrazag Nami; Ali Tumi; Abdulfattah Fitouri; Ahlam Ellafi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Helicobacter pylori (H. pylori) infections occur earlier in life with high on geographic area, socioeconomic status, and age of the host infected. Virulence factors of H. pylori such as cag pathogenicity island (cagPAI) have been demonstrated to be predictors of gastric diseases. In Libya, there is no data available regarding the prevalence of H. pylori infection in adults dyspeptic, & healthy blood donors. This study was conducted to determine the current prevalence of H. pylori and its relationship with age, gender, CagA status among healthy blood donors & adult dyspeptic, patients attending Teaching Hospitals in Tripoli. Methods. A Blood sample of (125) dyspeptic & (175) Healthy Blood Donors participants, anti-H. pylori IgG & anti-CagA IgG seroprevalence were determined with ELISA method (Biotech USA). Questionnaire covering sociodemographic variables were completed by interview. Results. The overall, seroprevalence of H. pylori was (83%), & (85%) in dyspeptic, & healthy blood donors respectively. There was a gradual increase with age. No statistical difference between genders. However, cagA status in H. pylori strains was 28%, 29.5% in dyspeptic & healthy blood donors respectively. Conclusions. The detection of the H. pylori pathogenicity marker (CagA) is crucial for reducing severe gastrointestinal disease in Libya. Larger studies and molecular techniques are needed to determine the genotype of H. pylori strains.